2014
DOI: 10.1590/0102-311x00169312
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with recurrent Plasmodium vivax malaria in Porto Velho, Rondônia State, Brazil, 2009

Abstract: This open retrospective cohort study aimed to describe the incidence of recurrent Plasmodium vivax malaria and associated factors in Porto Velho, Rondônia State, Brazil, in 2009. Data were collected from the National Information System for Malaria Epidemiological Surveillance. There were 23,365 reported P. vivax malaria cases in 2009, 23% of which were classified as relapses. Incidence density of P. vivax recurrence was 45.1/100 patient-years, mostly occurring between the 4th and 13th week after initiating tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 26 publications
4
24
0
4
Order By: Relevance
“…Despite this caveat, we believe the observed late recurrences indicate the existence of low-grade resistance to CQ, which would suppress but not completely eliminate circulating parasites [12]. This is based on 2 important assumptions: very low risk of reinfection, as most patients (90.5%) resided in urban areas with no active malaria transmission [23], and negligible contribution of relapses, which usually occur after day 35 in the region [32, 45, 46]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite this caveat, we believe the observed late recurrences indicate the existence of low-grade resistance to CQ, which would suppress but not completely eliminate circulating parasites [12]. This is based on 2 important assumptions: very low risk of reinfection, as most patients (90.5%) resided in urban areas with no active malaria transmission [23], and negligible contribution of relapses, which usually occur after day 35 in the region [32, 45, 46]. …”
Section: Discussionmentioning
confidence: 99%
“…Using routine surveillance data, the number of P. vivax episodes per person per year was evaluated for 2011 to show that from 23,365 reported episodes at least 23% could be classified as possible relapses. In this study, the number of episodes per person varied from one to more than seven,30 despite regular prescription of primaquine. The median time reported from the first episode to first recurrence was 65 days, longer than expected, and the interval to subsequent episodes tended to decrease progressively 30.…”
Section: Plasmodium Vivax Epidemiologymentioning
confidence: 87%
“…In this study, the number of episodes per person varied from one to more than seven,30 despite regular prescription of primaquine. The median time reported from the first episode to first recurrence was 65 days, longer than expected, and the interval to subsequent episodes tended to decrease progressively 30. However, the NMCP operational definition classifies episodes occurring within 60 days as relapses, leading to possible missed relapses that occur with longer intervals as well as to inappropriate classification as reinfection and recrudescence can also be an important cause of repeated episodes within this interval range.…”
Section: Plasmodium Vivax Epidemiologymentioning
confidence: 87%
“… 19 Studies have also identified that the events of vivax relapse are associated with patient and parasite factors. 20 , 21 …”
Section: Hypnozoites and Relapse Of Malariamentioning
confidence: 99%